2020
DOI: 10.1186/s12876-020-01502-w
|View full text |Cite
|
Sign up to set email alerts
|

A hypocaloric high-protein diet supplemented with β-cryptoxanthin improves non-alcoholic fatty liver disease: a randomized controlled trial

Abstract: Background Despite promising animal data, there is no randomized controlled trial (RCT) on the effects of high protein (HP)-diet and/or β-cryptoxanthin in non-alcoholic fatty liver disease (NAFLD). Aims: Safety and efficacy assessment of a hypocaloric HP-diet supplemented with β-cryptoxanthin in NAFLD. Methods Ninety-two Iranian NAFLD outpatients were recruited for this 12-week, single-center, parallel-group, double-blind RCT and randomized into 4 arms (n = 23): HP-diet and β-cryptoxanthin (hypocaloric HP-di… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Among the 137 studies 13–145 reported the results of the BMI, serum metabolism profiles (TG, LDL‐C and IR) and liver injury markers were reported. In Figure 4, for BMI, there were 5,572 patients in total, 39 treatment schemes, and another 2,302 patients as the control group (the corresponding network plots are shown in Figure 5A).…”
Section: Resultsmentioning
confidence: 99%
“…Among the 137 studies 13–145 reported the results of the BMI, serum metabolism profiles (TG, LDL‐C and IR) and liver injury markers were reported. In Figure 4, for BMI, there were 5,572 patients in total, 39 treatment schemes, and another 2,302 patients as the control group (the corresponding network plots are shown in Figure 5A).…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have examined the impact of high-protein diets, often in combination with a hypocaloric regimen and LCD, on hepatic health. In an Iranian study of 92 patients who underwent a hypocaloric high-protein diet (25% of energy intake) with or without the addition of antioxidant βcryptoxanthin, the high-protein groups showed a greater reduction in liver enzymes, but weight loss may have mediated this effect [16]. Among 19 bariatric patients, a hypocaloric high-protein diet (30% of energy intake) over 3 weeks prior to surgery led to a decrease of steatosis by 42.6% compared to no effect under identical energy but lower protein intake [67].…”
Section: Protein Contentmentioning
confidence: 99%
“…The available human intervention trials examining the effect of β-cryptoxanthin supplementation on a variety of outcomes have reported oral doses ranging from 0.75 mg/day to 6 mg/day [ 14 , 18 , 19 , 20 , 21 ], with no major adverse reactions [ 18 , 20 ]. To date, only one study has involved supplemental ingestion of a β-cryptoxanthin in a purified form [ 18 ], whilst the remaining studies have used beverages or concentrates of tangerine enriched in β-cryptoxanthin [ 14 , 19 , 20 , 21 ]. These studies have reported on a range of endpoints, including the combined effect of β-cryptoxanthin supplements with a hypocaloric diet for 12 weeks on circulating liver enzyme status in NAFLD patients [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…To date, only one study has involved supplemental ingestion of a β-cryptoxanthin in a purified form [ 18 ], whilst the remaining studies have used beverages or concentrates of tangerine enriched in β-cryptoxanthin [ 14 , 19 , 20 , 21 ]. These studies have reported on a range of endpoints, including the combined effect of β-cryptoxanthin supplements with a hypocaloric diet for 12 weeks on circulating liver enzyme status in NAFLD patients [ 18 ]. Further studies examining the actions of a Satsuma mandarin juice extract, containing β-cryptoxanthin, have demonstrated altered bone turnover markers in menopausal women [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation